BIOLOGY OF THE MEALYBUG PHENACOCCUS BENGALEANSIS PRAMANIK AND GHOSE, 1999 (HOMOPTERA: PSEUDOCOCCIDAE) - MISHRA, D.; MUKHOPADHYAY, A.K.; PRAMANLIK, A. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2004)
Biology of the mealybug, Phenacoccus bengalensis Pramanik and Ghose was studied on sprouted potato tubers in the laboratory at 28.8 to 32 °C and 88-96% R.H. The nymphs completed their ecdysis at the age of 20.01 it 2.32 days and all of them became adult females. The females started oviposition at the age of 31-42 days. The preoviposition and oviposition period, fecundity and incubation period of eggs are 14.20 + 1.93 days, 9.08 + 1.89 days, 67.42 + 8.62 eggs/female and 4.57 E 1.55 days, respectively. The starvation of females had little effect by reducing 22.28% fecundity and 18.50% oviposition period. The longevity of adult female ranged from 47-55 (50 + 2.94) days and the species reproduces parthenogenetically.